Comments on gas demand, contracts and prices - Jensen, J; Oxford Institute for Energy Studies (2008)
The February issue of the Oxford Energy Forum contained five excellent articles on the future role of natural gas. There appear to be two recurring themes – strong growth in gas demand and issues of contracting and pricing.